Cognitive deficits in acute mild ischemic stroke and TIA and effects of rt‐PA - Rosenbaum Halevi, David (John Wiley and Sons Inc., 2019)

(untitled) (Ann Clin Transl Neurol)
INTRODUCTION: It is unknown if treatment with rt‐PA in mild acute ischemic stroke (MIS) is associated with improvement in long term cognition. METHODS: Forty‐five patients with suspected acute mild stroke or transient ischemic attacks with NIHSS ≤6 were enrolled in a prospective cohort. Cognitive testing was performed within 24 h of symptom onset. Follow‐up assessment was performed at Day 90 on 25 patients. Prestroke baseline cognition was based on age, years of education (YrE), history of cognitive impairment, and the Fazekas score. RESULTS: Eighty‐five percent patients with suspected MIS or TIA showed cognitive abnormalities within 24 h of onset. There was no significant difference in age, sex, Fazekas score, or YrE between rt‐PA versus No‐rt‐PA groups (N = 8 vs. 17).Two sample t‐test for change in performance in the WMS‐III sub‐tests (follow‐up – baseline) ± SD, indicated a difference between rt‐PA 0.74 ± 0.77 and no‐rt‐PA groups ‐0.02 ± 0.83 (P = 0.044). Logistic regression for predicting normal status using the mental control subtest, at follow‐up showed an OR 8.96, CI 0.98–82.12 (P = 0.05) favoring the rt‐PA group. Improvement in Mental Control at 90 days occurred in patients with low white matter disease compared to high white matter disease, 0.60 ± 0.46 (P = 0.048). A statistical trend was observed and suggested an improvement on SDMT and Trail Making tests, 1.43 ± 0.8 (P = 0.077). CONCLUSION: Suspected MIS and TIA patients have cognitive impairment within 24 h of onset. rt‐PA administration might be associated with improvement on some cognitive tests at 90 days.